Clinical diagnosis of bilateral vestibular loss: three simple bedside tests. (January 2013) - Petersen, Jens A.; Straumann, Dominik; Weber, Konrad P.
Bilateral vestibular loss (BVL) may present with or without vertigo and hearing loss. Amongst the causes of BVL are vestibulotoxic antibiotics, autoimmune ear diseases, Menière's disease and meningitis. Clinical diagnosis of BVL is based on the result of three simple bedside tests: a positive head impulse test, reduced dynamic visual acuity and a positive Romberg test on foam rubber. With these signs, diagnosis of severe BVL is usually straightforward to establish.